SYLLABLE RHYTHM AND PROSODY: THE THEORY OF CLASSIFICATION OF LANGUAGES BY RHYTHM AND THE MANIFESTATION OF ISOCHRONY IN THE POETIC SYSTEM (Scientific journal of the Fergana State University, 2026)
Theories explaining the linguistic phenomena that constitute the poetic system of syllabic  rhythm are subjected to analytical analysis in the article. It is noted that syllabic meter is a versification system with a wide geographical area and historical depth. The reasons for the appearance of this meter in the literature of languages ​​​​where syllables are of relatively equal length and stress plays a less dominant role in the rhythm of speech are explained by the classification of languages ​​​​according to rhythm and the theory of isochrony. The emergence of syllabic meter and forms in the literature of different peoples is based on the phonetic patterns of that language, phonological phenomena, and prosody laws. The rhythmic classification of languages ​​and the theory of isochrony are analytical study or hypotheses that suggest that the utterances of any spoken language can be divided into some kind of equal parts. According to this hypothesis, languages ​​are divided into two categories based on rhythm or temporality and the division creates the rhythm of speech, which in turn creates the poetic meter of that language.